The Role of Motivation in the Knowledge Transfer of Employees - Sanja Gutić Martinčić (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Virtual Conference, 10-12 September 2020, 2020)
Human resource management emphasizes significantly more effort in acquiring new knowledge than it does in transferring acquired knowledge. The research aims to determine how much motivation of the individuals can influence to transfer their knowledge to other employees. The research focuses on the meaning of motivation in knowledge transfer. It was conducted by direct survey in 2019 on a quota sample of 110 respondents. Sampling was performed from several medium-sized organizations from different activities in the three counties of North-Western Croatia. The questionnaire was constructed using the five-level Liker's scale model and had 24 items or motivators for knowledge transfer. These are also independent variables: expected reward for knowledge transfer, job satisfaction, training effects, compassionate empathy, personal responsibility, position in the organization, experience in knowledge transfer, loyalty to the organization. The reliability of the scales was tested by Cronbach alpha indicators. The multiple regression analysis methods were applied. It was found that the position in the organization participates most in the motivators for knowledge transfer, followed by the expected reward for knowledge transfer. Interestingly, the variables job satisfaction, experience in knowledge transfer and loyalty to the organization had almost no role in transferring knowledge to other employees.
Keywords: O15; 330; employees; knowledge; transfer; motivation